Effects of service quality and customer satisfaction on loyalty of bank customers - Achmad Supriyanto (Cogent Business & Management, 2021)
Service quality and customer satisfaction are parts of factors that influence customer loyalty to bank services. Both are necessary to be fulfilled in order to gain customer loyalty, which in turn maintaining organization survival in the long term. This study aims to (1) examine how service quality influenced customer loyalty; (2) how customers’ satisfaction influenced their loyalty to the bank; and (3) examine simultaneous effects of service quality and customer satisfaction on customer loyalty. This study used a survey research design, and respondents were selected purposively from a population of Bank organization in Indonesia. Data were analyzed employing path analysis and One-Way Analysis of Variance. Results indicate that service quality did not have significant effects on customer loyalty, but it provided significant effects on customer satisfaction followed by influencing customer loyalty. Service quality had indirect effects on customer loyalty through customer satisfaction. Further studies are expected to examine the model of relationships with other variables.